KINETICS OF LEAD ADSORPTION BY IRON OXIDES FORMED UNDER THE INFLUENCE OF CITRATE - Liu C.; Huang P.M. (My University, 2003)
The presence of organic acids greatly affects the formation of Fe oxides and surface properties; however, the subsequent effect on the kinetics and mechanisms of Pb adsorption by the Fe oxides formed under the influence of organic acids remains obscure. The kinetics of Pb adsorption on the Fe oxides formed in the presence of citrate ligands at initial citrate/Fe(II) molar ratios (MRs) of 0, 0.001, 0.01, and 0.1 was studied at the initial Pb concentration of 8.33 μM and pH 5.0 at 278, 288, 298, and 313 K using macroscopic batch method. The results indicate that the Pb adsorption followed multiple first-order kinetics and the rate coefficient, activation energy, and pre-exponential factor in the Arrhenius equation of the adsorption varied greatly with the surface properties of the Fe oxides formed at various citrate/Fe(II) MRs. The alteration of surface properties of Fe oxides formed at the citrate/Fe(II) MR of 0.1 and the effect on the rate coefficient of the fast and slow reactions of Pb adsorption were especially significant. The rate-limiting step of Pb adsorption reactions on the Fe oxides was predominantly a diffusion process, except for the slow reaction of Pb adsorption on the Fe oxides formed at the initial citrate/Fe(II) MR of 0.1, where the rate-limiting process was evidently a chemical process, which may involve bond breaking between the coprecipitated citrate ligand and Fe oxide. The rate coefficients of Pb adsorption by the Fe oxides formed at various citrate/Fe(II) MRs cannot be explained by the activation energy alone. The pre-exponential factor plays an important role in influencing the rate coefficient of Pb adsorption by the Fe oxides. The role of organic acids such as citric acid in influencing the crystallization and the resultant alteration of surface properties of Fe oxides, and the impact on the dynamics of Pb in terrestrial and aquatic environments, thus merit close attention.